2019
DOI: 10.1038/s41419-019-1891-8
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8-androgen receptor association within lipid rafts promotes prostate cancer cell migration

Abstract: In prostate carcinogenesis, androgens are known to control the expression of the transient receptor potential melastatin 8 (TRPM8) protein via activation of androgen receptor (AR). Overexpression and/or activity of TRPM8 channel was shown to suppress prostate cancer (PCa) cell migration. Here we report that at certain concentrations androgens facilitate PCa cell migration. We show that underlying mechanism is inhibition of TRPM8 by activated AR which interacts with the channel within lipid rafts microdomains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 49 publications
3
51
0
Order By: Relevance
“…This inhibition was produced by the activated AR interacting with the channel present within lipid-raft domains. Grolez et al (2019) proposed that the differences between their results and those from Asutkhar et al (2015) might be explained by the differences in the design of the experiments since the former study used lipid bilayers and cells lacking the AR receptor, as well as lower concentrations of testosterone. Thus, the elucidation of the precise molecular mechanism of androgen regulation of TRPM8 channels requires further investigation.…”
Section: Ion Channel Regulation By Androgensmentioning
confidence: 88%
See 2 more Smart Citations
“…This inhibition was produced by the activated AR interacting with the channel present within lipid-raft domains. Grolez et al (2019) proposed that the differences between their results and those from Asutkhar et al (2015) might be explained by the differences in the design of the experiments since the former study used lipid bilayers and cells lacking the AR receptor, as well as lower concentrations of testosterone. Thus, the elucidation of the precise molecular mechanism of androgen regulation of TRPM8 channels requires further investigation.…”
Section: Ion Channel Regulation By Androgensmentioning
confidence: 88%
“…The binding of testosterone was decreased by the presence of TRPM 8 agonists such as menthol (50 mM), icilin (10 mM), and M8-B (1 mM). However, Grolez et al (2019) showed that, testosterone (10 nM) inhibited the transient increase of the intracellular calcium concentration induced by icillin (10 mM) in the presence of the AR. These results suggest that at some concentrations, testosterone inhibits the activity of TRPM8 via an ARdependent mechanism.…”
Section: Ion Channel Regulation By Androgensmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, cholesterol-rich lipid rafts have been found to act as sites of intersection of androgen receptor (110 kDa) and AKT signaling in prostate cancer cells (177). Androgen receptor plays a major role in the pathogenesis of prostate cancer (178), and a functional interaction between transient receptor potential melastatin 8 (TRPM8) and androgen receptor in lipid rafts has been shown to promote cancer cell migration (179). (193).…”
Section: Estrogen Receptormentioning
confidence: 99%
“…Furthermore, the TRPM8 agonist WS12 encapsulated into lipid nanocapsules is able to impair cancer cell migration ability [51]. On the other hand, testosterone is able to inhibit TRPM8 activity [52]. Indeed, low (10 nM), but not high (100 nM), testosterone concentrations decrease TRPM8-mediated Ca 2+ influx, resulting in a significant increase in cell migration.…”
Section: Trpm Channels In Cancer Therapymentioning
confidence: 99%